2020
DOI: 10.37121/ijesr.vol1.135
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of an Effective Solid Wastes Collection at the Workplace: the Experience of the Council for Scientific and Industrial Research-Institute of Industrial Research, Accra, Ghana

Abstract: The inefficient collection of solid wastes is a global phenomenon that has received attention in recent years for the ever-increasing annual waste generation records. However, indicators to the effective application of the amassing routs are missing. Hence, the generally accepted source-sorting model was explored to identify the determinants that will enhance source separation of wastes at the workplace. This paper presents a foremost report on the indicators to an effective operation of solid wastes source se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…A study of staff preferences towards the mode of waste collection at the work place showed a significant interest of workers to source separate their wastes for enhanced recycling activities (Antwi et al, 2019). The implementation of literature and survey findings by the provision of adequate twin-dustbin setups with different colour codes for the source separation of solid wastes at the CSIR-IIR, demonstrated a 65% source segregation of generated wastes (Antwi et al, 2020). This estimates the potential benefits that will be achieved on a scaled-up institutional source sorting process.…”
Section: Introductionmentioning
confidence: 85%
“…A study of staff preferences towards the mode of waste collection at the work place showed a significant interest of workers to source separate their wastes for enhanced recycling activities (Antwi et al, 2019). The implementation of literature and survey findings by the provision of adequate twin-dustbin setups with different colour codes for the source separation of solid wastes at the CSIR-IIR, demonstrated a 65% source segregation of generated wastes (Antwi et al, 2020). This estimates the potential benefits that will be achieved on a scaled-up institutional source sorting process.…”
Section: Introductionmentioning
confidence: 85%